Short-time work: The German answer to the Great Recession - Karl Brenke; Ulf Rinne; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2011)
Short-time work was the German answer to the economic crisis. The number of short-time workers strongly increased in the recession and peaked at more than 1.5 million. Without the extensive use of short-time work, unemployment would have risen by approximately twice as much as it actually did. Short-time work has certainly contributed to the mild response of the German labor market to the crisis, but this is likely due to the country-specific context. Although the crisis has been overcome and employment is strongly expanding, modified regulations governing short-time work are still in place. This leads to undesired side effects.
urn:nbn:de:101:1-20110621407
Keywords: J65; J68; 330; labor market policy; partially unemployed workers; short-time work compensation; economic crisis